Prevalence of Measles in children aged 0-59 months at the Kindu General Referral Hospital from 01-06-2024 to 30-06-2025 - SHAKO SALAMA; Janvier BAMBALATI SABITI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
By undertaking this study which focuses on the prevalence of Measles among Children Aged 0–59 Months at the General Reference Hospital of Kindu from June 1, 2024, to June 30, 2025, aimed to determine the frequency and mortality rate related to measles in this age group. A retrospective and prospective analysis was conducted among 353 pediatric admissions, including 36 measles cases, giving a prevalence rate of 10.2%. The male gender was predominant (61.1%), and the most affected age group was 6–12 months (44.4%). Children living outside the health area accounted for 66.6% of cases, and the mortality rate was 44.4%, indicating a serious health concern. Most of the affected children (66.6%) were not fully vaccinated. The study highlights the persistence of measles in Kindu, mainly due to low vaccination coverage and delayed hospital referrals. Recommendations were made to strengthen community awareness, train healthcare workers, and improve vaccination coverage to reduce measles-related morbidity and mortality.